Characterization of a Novel Drosophila Sert Mutant: Insights on the Contribution of the Serotonin Neural System to Behaviors - Reyes-Parada, M (American Chemical Society, 2017)
A better comprehension on how different molecular components of the serotonergic system contribute to the adequate regulation of behaviors in animals is essential in the interpretation on how they are involved in neuropsychiatric and pathological disorders. It is possible to study these components in "simpler" animal models including the fly Drosophila melanogaster, given that most of the components of the serotonergic system are conserved between vertebrates and invertebrates. Here we decided to advance our understanding on how the serotonin plasma membrane transporter (SERT) contributes to serotonergic neurotransmission and behaviors in Drosophila. In doing this, we characterized for the first time a mutant for Drosophila SERT (dSERT) and additionally used a highly selective serotonin-releasing drug, 4-methylthioamphetamine (4-MTA), whose mechanism of action involves the SERT protein. Our results show that dSERT mutant animals exhibit an increased survival rate in stress conditions, increased basal motor behavior, and decreased levels in an anxiety-related parameter, centrophobism. We also show that 4-MTA increases the negative chemotaxis toward a strong aversive odorant, benzaldehyde. Our neurochemical data suggest that this effect is mediated by dSERT and depends on the 4-MTA-increased release of serotonin in the fly brain. Our in silico data support the idea that these effects are explained by specific interactions between 4-MTA and dSERT. In sum, our neurochemical, in silico, and behavioral analyses demonstrate the critical importance of the serotonergic system and particularly dSERT functioning in modulating several behaviors in Drosophila. © 2017 American Chemical Society.